CAN HYPOCRISY BE A VIRTUE? HUME ON THE MORALITY OF PRINCES - Abranches, Alexandra (Ethics, Politics & Society, 2023)
This paper examines the moral status of hypocrisy in the moral and political philosophy of David Hume. Its aim will be to try to determine whether, according to Hume, hypocrisy has any positive moral value, or whether, not having any, Hume should therefore be placed in the same category of political realists such as Machiavelli, with his sharp distinction between moral and political values. If the latter is the case, then hypocrisy can be described as an absolute moral vice. But if the former is the case, that is, if hypocrisy has any moral value, then Hume does not support the sharp separation between what is right from a political and from a moral point of view, which means that there may even be, then, some relation between hypocrisy and moral obligation. In other words, hypocrisy may very well be virtuous.